A Self-starting AC-to-DC Step-up Converter for Energy Harvesting Applications - Phattharapol Choetchai; Apinunt Thanachayanont (My University, 2016)
This paper presents the design and implementation of a self-starting direct AC-to-DC step-up converter for energy harvesting applications. The proposed circuit employs a power efficient buck-boost converter with a diode voltage multiplier as a start-up circuit. The overall AC-to-DC converter can start and run autonomously from an audio signal generator, such as an audio jack. Experimental results showed that the prototype converter could achieve a power conversion efficiency of 45% when applying a 5-kHz input signal.
Keywords: Buck converter; Voltage multiplier; Innovative Energy Harvesting Technologies